(untitled) (Ukrainian Journal of Ophthalmology, 2025)
The prevalence of myopia has been steadily increasing worldwide. The role of optical methods for controlling progressive myopia control in children is still important. Therefore, the purpose of this study was to review current optical methods for controlling progressive myopia control in children. It is well established that myopic children wearing full optical correction are less prone to the progression of the disease. It has been reported that the undercorrected group of myopic school children showed a 1.3 times greater rate of progression over 24 months as compared to the fully corrected group. Correction of myopia with spectacles is common in children. Many clinicians share the opinion that myopic peripheral defocus has a positive effect on axial elongation, and peripheral defocus spectacles have been increasingly used for this purpose. Optical correction with spectacles, however, may have some disadvantages. Some children wearing spectacles may feel psychological discomfort due to negative peer comments and/or have problems with compliance. Soft contact lenses with myopic defocus and othokeratology (OK) lenses are of special value for myopia progression control. It has been reported that myopia progression was controlled by 38.6% and 66.6% in children wearing Multistage + 1.50D and Proclear +3.00D multifocal contact lenses, respectively, in comparison to children wearing single-vision control lenses over an 18-month period. Refractive therapy with orthokeratology lenses has become an increasingly popular technique for controlling the progression of myopia. It has been reported that orthokeratology lenses are more effective than spectacles or soft contact lenses at reducing myopia progression. The review provides evidence that myopia control devices utilizing the myopic defocus principle are the first-line means for optical correction in children with progressive myopia.